If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1 = 4x + -6(x + 5) Reorder the terms: -1 + 2x = 4x + -6(x + 5) Reorder the terms: -1 + 2x = 4x + -6(5 + x) -1 + 2x = 4x + (5 * -6 + x * -6) -1 + 2x = 4x + (-30 + -6x) Reorder the terms: -1 + 2x = -30 + 4x + -6x Combine like terms: 4x + -6x = -2x -1 + 2x = -30 + -2x Solving -1 + 2x = -30 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -1 + 2x + 2x = -30 + -2x + 2x Combine like terms: 2x + 2x = 4x -1 + 4x = -30 + -2x + 2x Combine like terms: -2x + 2x = 0 -1 + 4x = -30 + 0 -1 + 4x = -30 Add '1' to each side of the equation. -1 + 1 + 4x = -30 + 1 Combine like terms: -1 + 1 = 0 0 + 4x = -30 + 1 4x = -30 + 1 Combine like terms: -30 + 1 = -29 4x = -29 Divide each side by '4'. x = -7.25 Simplifying x = -7.25
| 0.99+0.07=1.83 | | 3(4+2x)-3x=-18 | | 3x+30=6(-4x-4) | | (3x^2+x-4)+(2x^2+2x-3)= | | y=9E+(06*2015)-2E+10 | | -5(-x+1)=-15 | | 1/3x=7.8 | | x=-6-4 | | p=25t+50 | | 3x^2-5x+6.25=0 | | r-7/16=-1 | | L+-45=77 | | F(x)=x^2+8x-10 | | (2x^2/9)(27/8x^5) | | x+16-2=27 | | 1y/3=1/3-1/2y | | √48x^3/√3 | | M+6-3m= | | 3-s=6tj+10 | | -6r-1-13r=18 | | 2b+5-8b=11 | | -5w=-125 | | 16-5(3x-4)=8(11-2x) | | 5+2t=12+18t-4.905t^2 | | 8(-4x+y-2)= | | 15x-5=3x+7 | | 3x-7=2(x-5) | | 2lnx-4ln(4x)=2 | | 3-4n=2n+3 | | A-45=-78 | | 9h(7h^2)= | | 7x+11(1)=4 |